2019
DOI: 10.1016/j.cell.2018.12.032
|View full text |Cite
|
Sign up to set email alerts
|

A Tradeoff in the Neural Code across Regions and Species

Abstract: Summary Many evolutionary years separate humans and macaques, and whereas the amygdala and cingulate-cortex evolved to enable emotion and cognition in both, an evident functional gap exists. Although it was traditionally attributed to differential neuroanatomy, functional differences might also arise from coding mechanisms. Here, we find that human neurons better utilize information capacity (efficient coding) than macaque neurons, in both regions; and that cingulate neurons are more efficient than amygdala ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 72 publications
(154 reference statements)
4
61
0
2
Order By: Relevance
“…While medial-tract neurons are involved in odor identification and establishment of odor memory – functions that require fine-tuning and precision - the uni-lateral lateral-tract neurons could serve a more direct role for fast control of key behaviors, requiring strength and sturdiness. Interestingly, these observations are in line with the robustness–efficiency trade-off hypothesis, stating that neural coding cannot be simultaneously optimized for robustness and efficiency, i. e. information capacity (Pryluk et al, 2019). The observed division of labor between neurons of the medial and lateral ALT thus might be an implementation of this tradeoff.…”
Section: Discussionsupporting
confidence: 75%
“…While medial-tract neurons are involved in odor identification and establishment of odor memory – functions that require fine-tuning and precision - the uni-lateral lateral-tract neurons could serve a more direct role for fast control of key behaviors, requiring strength and sturdiness. Interestingly, these observations are in line with the robustness–efficiency trade-off hypothesis, stating that neural coding cannot be simultaneously optimized for robustness and efficiency, i. e. information capacity (Pryluk et al, 2019). The observed division of labor between neurons of the medial and lateral ALT thus might be an implementation of this tradeoff.…”
Section: Discussionsupporting
confidence: 75%
“…Our conclusion fits the optimal feedback control theory, which postulates that motor systems selectively use feedback information to optimize an index of performance by combining sensory signals and motor commands [54][55][56]. For the CNS, this solution must come at the cost of reducing the accuracy or, as others called it, optimality [23] or 235 efficiency [57]. Here, we found a clear widening of motor primitives at increasing locomotion speeds, but only in the synergies relevant for the stance phase (i.e.…”
Section: Longer Less Complex Motor Primitives Ensure Robust Control supporting
confidence: 67%
“…We reasoned that the overlap of chronologically-adjacent synergies increased the fuzziness (9, 36) of temporal boundaries allowing for easier shifts between one synergy (or gait phase) to the other (7), a conclusion that fits the optimal feedback control theory (37,38). For the CNS, 30 this solution must come at a cost: the reduction of accuracy or, as others called it, optimality (9) or efficiency (39). For instance, it has been recently found that human neurons allow less vocabulary overlap than monkey's, showing a tradeoff between accuracy (complex human feature) and robustness (basic, typical of non-human primates) across species (39).…”
Section: Discussionmentioning
confidence: 99%
“…For the CNS, 30 this solution must come at a cost: the reduction of accuracy or, as others called it, optimality (9) or efficiency (39). For instance, it has been recently found that human neurons allow less vocabulary overlap than monkey's, showing a tradeoff between accuracy (complex human feature) and robustness (basic, typical of non-human primates) across species (39). In this study we confirmed a widening of motor primitives in those conditions that were more constrained 35 than their equivalent baseline and in aging.…”
Section: Discussionmentioning
confidence: 99%